No yield penalty under favorable conditions paving the way for successful adoption of flood tolerant rice - Dar, Manzoor H.; Zaidi, Najam W.; Waza, Showkat A.; Verulkar, Satish B.; Ahmed, T.; Singh, P.K.; Roy, S. K. Bardhan; Chaudhary, Bedanand; Yadav, Rambaran; Islam, Mirza Mofazzal; Iftekharuddaula, Khandakar M.; Roy, J.K.; et al. (Springer, 2018)
Flooding is one of the major constraints for rice production in rainfed lowlands, especially in years and areas of high rainfall. Incorporating the Sub1 (Submergence1) gene into high yielding popular varieties has proven to be the most feasible approach to sustain rice production in submergence-prone areas. Introgression of this QTL into popular varieties has resulted in considerable improvement in yield after flooding. However, its impact under non-flooded conditions or years have not been thoroughly evaluated which is important for the farmers to accept and adopt any new version of their popular varieties. The present study was carried out to evaluate the effect of Sub1 on grain yield of rice in different genetic backgrounds, under non-submergence conditions, over years and locations. The study was carried out using head to head trials in farmer’s fields, which enable the farmers to more accurately compare the performance of Sub1 varieties with their recurrent parents under own management. The data generated from different head to head trials revealed that the grain yield of Sub1 varieties was either statistically similar or higher than their non-Sub1 counterparts under non-submergence conditions. Thus, Sub1 rice varieties show no instance of yield penalty of the introgressed gene.